The omnichord real book [compact disc] - NdegéOcello, Me'Shell, 1969-; Johnson, Josh (Saxophonist); Hicks, Jade; Parks, Deantoni, 1977-; Parker, Jeff (Jazz guitarist); Biggers, Sanford; Henry, Cory; Ross, Joel, 1996-; Moran, Jason; Thandiswa; Younger, Brandee; Rodriguez, Julius; et al. (Blue Note, 2023)
Meshell Ndegeocello returns with an album of new original material that taps into a broad spectrum of her musical roots. The Omnichord Real Book was produced by Josh Johnson and features a wide range of guest artists including Jason Moran, Ambrose Akinmusire, Joel Ross, Jeff Parker, Brandee Younger, Julius Rodriguez, Mark Guiliana, Cory Henry, Joan As Police Woman, Thandiswa, and others.